Inpatient characteristics of the child admitted with chronic pain - Coffelt, Thomas A; Bauer, Benjamin D; Carroll, Aaron E (Pediatrics (Evanston), 2013)
To define the demographic, diagnostic, procedural, and episode of care characteristics for children admitted with chronic pain. We used the Pediatric Health Information System database to obtain data on demographic characteristics, length of stay, readmission rates, diagnoses, and procedures for children admitted with chronic pain. Patients with sickle cell disease, cancer, burns, cerebral palsy, transplants, and ventilator-dependent children were excluded. A total of 3752 patients with chronic pain were identified from 2004 through 2010. Admissions increased by 831% over this time period. The mean age of these patients was 13.5 years, the most common race was white (79%), and female subjects outnumbered male subjects by 2.41 to 1. The most common admission and principal discharge diagnosis was abdominal pain; comorbid diagnoses were common, with a mean of 10 diagnoses per patient. In total, 65% of patients had a comorbid gastrointestinal diagnosis and 44% had a psychiatric diagnosis. The mean length of stay was 7.32 days, with an expected length of stay of 4.24 days; 12.5% were readmitted at least once within 1 year. They underwent a mean of 3.18 procedures per patient. The average child admitted with chronic pain is a teenaged female with a wide variety of comorbid conditions, many of which are gastrointestinal and psychiatric in nature. Admissions for chronic pain are rising and account for substantial resource utilization. Future studies should further characterize this population, with the overall objective of improving outcomes and optimizing cost-effective care.